PENGGUNAAN PROGRAM LINEAR DUAL UNTUK MENYELESAIKAN MASALAH LOKASI FASILITAS TAK TERBATAS - , TYAS AGUSTINA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In this thesis, we present a solution of an uncapacitated facility location problem. The problem consists of choosing some facilities and allocating a set of customers to these facility locations such that minimizing the total cost and computing the total price paid by each customer. Accordingly, the problem is solved by using a method based on dual linear programming. The method consists of three algorithms that is done and consecutively. First, the dual ascent algorithm is used to compute a solution of dual linear programming. Second, the primal algorithm is used to determine some of facility locations that will be opened and to allocate a set of customers to these facility locations. Third, the dual adjustment algorithm is used to adjust the dual solution in case the dual ascent algorithm and the primal algorithm cannot find an optimal solution. As an illustration, at the end of this thesis we present an implementation of the three algorithms.